2006
DOI: 10.1136/gut.2005.087452
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic indications for endoscopic mucosal resection of laterally spreading tumours in the colorectum

Abstract: Background: Laterally spreading tumours (LSTs) in the colorectum are usually removed by endoscopic mucosal resection (EMR) even when large in size. LSTs with deeper submucosal (sm) invasion, however, should not be treated by EMR because of the higher risk of lymph node metastasis. Aims: To determine which endoscopic criteria, including high magnification pit pattern analysis, are associated with sm invasion in LSTs and clarify indications for EMR. Methods: Eight endoscopic criteria from 511 colorectal LSTs (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
359
1
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(388 citation statements)
references
References 24 publications
(20 reference statements)
13
359
1
15
Order By: Relevance
“…When analyzing the endoscopic features of 257 LSTs in order to assess which features correlated with the depth of invasion, unevenness of nodules, presence of large nodules, size, histological type, and presence of depression in the tumor were significantly associated with the depth of invasion [41] . In addition, LST-NG showed a higher frequency of sm invasion than LST-G (14% vs 7%) [42] . Presence of a large nodule in LST-G type was associated with higher sm invasion while pit pattern, sclerous wall change, and larger size were significantly associated with higher sm invasion in LST-NG type.…”
Section: Endoscopic Resection Of Colorectal Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing the endoscopic features of 257 LSTs in order to assess which features correlated with the depth of invasion, unevenness of nodules, presence of large nodules, size, histological type, and presence of depression in the tumor were significantly associated with the depth of invasion [41] . In addition, LST-NG showed a higher frequency of sm invasion than LST-G (14% vs 7%) [42] . Presence of a large nodule in LST-G type was associated with higher sm invasion while pit pattern, sclerous wall change, and larger size were significantly associated with higher sm invasion in LST-NG type.…”
Section: Endoscopic Resection Of Colorectal Tumorsmentioning
confidence: 99%
“…Therefore, it is advisable to perform endoscopic piecemeal resection for LST-G type with the area including the large nodule resected first. Besides, LST-NG type should be removed by en bloc resection (Figure 3) because of the higher potential of sm invasion when compared to that of the LST-G type [42] . A study from Germany reported that complications occurred in two patients of 57 patients after EMR in large colorectal neoplasia between 10 mm and 50 mm [43] .…”
Section: Endoscopic Resection Of Colorectal Tumorsmentioning
confidence: 99%
“…3 LST are usually removed by endoscopic mucosal resection while in the presence of deeper sub-mucosal invasion they should be treated by surgery due to the higher risk of lymph node metastasis. 4 Here we briefly report a case of giant LST occurring in a patient with long-standing UC.…”
mentioning
confidence: 98%
“…LSTs can be further divided into two main classes: granular type (LST-G) and non-granular type (LST-NG) ( Figure 1). We know that LST-NG tumors of size more than (or equal to) 20 mm and LST-G tumors of size more than (or equal to) 30 mm harbor a significantly higher likelihood of submucosal invasion [12]; therefore, a careful evaluation of morphological features is crucial for the depth diagnosis.…”
Section: White-light Non-magnifying Endoscopymentioning
confidence: 99%